Decoding Wheat Endosphere–Rhizosphere Microbiomes in Rhizoctonia solani–Infested Soils Challenged by Streptomyces Biocontrol Agents - Araujo, Ricardo; Dunlap, Christopher; Barnett, Steve; Franco, Christopher M.M. (Frontiers in Plant Science, 2019)
The endosphere and the rhizosphere are pertinent milieus with microbial communities that perturb the agronomic traits of crop plants through beneficial or detrimental interactions. In this study we challenged these communities by adding Streptomyces biocontrol strains to wheat seeds in soils with severe Rhizoctonia solani infestation. Wheat plants were grown in a glasshouse standardized system and the bacterial and fungal microbiome of 233 samples of wheat roots (endosphere) and rhizosphere soils were monitored for 20 weeks, from seed to mature plant stage. The results showed highly dynamic and diverse microbial communities that changed over time, with Sphingomonas bacteria and Aspergillus, Dipodascus and Trichoderma fungi increasing over time. Application of biocontrol Streptomyces strains promoted plant growth and maturation of wheat heads and modulated the root microbiome, decreasing Paenibacillus and increasing other bacterial and fungal OTUs. The soils with the highest levels of R. solani had increased reads of Thanatephorus (Rhizoctonia anamorph) and increased root disease levels and increased Balneimonas, Massilia, Pseudomonas and unclassified Micrococcaceae. As we enter the era of biologically sustainable agriculture it may be possible to reduce and limit the effects of serious fungal infestations by promoting a beneficial microbiome through the application of biocontrol agents during different periods of plant development.